Faktor-Faktor Penyebab Putus Sekolah: Studi Kasus Tunggal pada Siswa SMK di Kabupaten Tasikmalaya - Siti Nur Aini Putri; Muhamad Fath Syulha Putra Supriadi; Salwa Dwinurhayani; Elvira Catraliya Putri Baktiono; Adhit Diana Hidayat (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
The dropout rate in vocational secondary education remains a crucial issue requiring in-depth handling. This study aims to describe and analyze the factors causing a student to drop out of a vocational high school (SMK) in Tasikmalaya Regency. This research is a qualitative study employing a single case study approach. Primary data sources were obtained through in-depth interview techniques with the research subject and the subject's parents located in the Manonjaya area, Tasikmalaya Regency. Data analysis was conducted by reducing data, displaying data, and drawing conclusions to understand the psychological and social dynamics experienced by the subject. The results indicate that the factors causing the subject to drop out are dominated by internal factors, including a mismatch of interest in the major, low formal learning motivation due to a strong desire to focus on Islamic boarding school (pesantren) education, and an introverted personality that hindered adjustment at school. External factors include pressure from parents to attend formal school, the influence of a peer environment that supported truant behavior, and discomfort regarding interactions with teachers. These findings are expected to serve as a reference for Guidance and Counseling teachers in conducting early detection through understanding students' interests and talents, as well as the importance of collaboration between